Rapid review: Recent advances in in vitro models for the study of Cryptosporidium parvum - Mathilde S. Varegg; Ian D. Woolsey; Lucy J. Robertson; Alejandro Jiménez-Meléndez (Current Research in Parasitology and Vector-Borne Diseases)
Cryptosporidium research has been hampered by the lack of in vitro models that can recapitulate the life cycle of the parasite, thus relying on repeated animal infections. Traditional in vitro systems, employing cancerous cell lines, have been unable to support sexual reproduction, but have been widely employed for drug screening assays and allowed transcriptome mapping of the parasite, but extrapolation of those results to in vivo infections is limited. In recent years, intestinal organoids (enteroids), grown as 3D structures, have come to be recognized as more physiologically relevant, complex systems, since they more accurately reproduce the cell populations present in the small intestine. A key advantage of these systems is their ability to fulfil the life cycle of the parasite. However, studies employing bovine organoids, the target species of the major zoonotic species Cryptosporidium parvum, are lacking. Future research should emphasize bioengineered systems, with heterogeneous populations of intestinal epithelial and mesenchymal cells, to advance the in vitro field closer to in vivo infection models. The present review summarizes the history of cell line use in Cryptosporidium research and the most recent advances in organoids, bio-engineered and organ-on-a-chip platforms, including methodological approaches used to facilitate exposure of the apical side of the target cells to the parasite, and the influence of mechanical forces and microenvironment.